Treatment of recurrent epileptic seizures in patients with neurological disorders - YUAN, GUAN-QIAN (D.A. Spandidos, 2013)
This study aimed to investigate the clinical characteristics and the treatment principles and methods of recurrent epileptic seizures in patients with neurological disorders. A retrospective analysis was performed of the clinical data, treatment methods and results in 13 patients with recurrent epileptic seizures attending the neurosurgery department. Of the 13 patients, 10 had a history of epilepsy, 9 had organic frontal lobe brain lesions and 11 exhibited frontal lobe epilepsy. The causes of the epileptic seizure aggravation included drug withdrawal, dose reduction and dressing change (5 cases). The epileptic seizure types included partial and secondary full seizures and the seizure frequency ranged from 1 seizure/3 min to 1 seizure/several h. Following combined therapy with multiple anti-epileptic drugs (AEDs), including oral administration and injection, the epilepsy was controlled. The addition of orally administered levetiracetam improved the treatment efficiency. In cases of recurrent epileptic seizures in patients with neurological disorders, the combined administration of AEDs should be conducted with doses higher than the conventional initial dose to control the epileptic seizures as rapidly as possible.